Quantum non-Markovianity: Overview and recent developments - Shrikant, U.; Mandayam, Prabha (Frontiers in Quantum Science and Technology, 2023)
In the current era of noisy intermediate-scale quantum (NISQ) devices, research in the theory of open system dynamics has a crucial role to play. In particular, understanding and quantifying memory effects in quantum systems is critical to gain a better handle on the effects of noise in quantum devices. The main focus of this review is to address the fundamental question of defining and characterizing such memory effects -- broadly referred to as quantum non-Markovianity -- from various approaches. We first discuss the two-time-parameter maps approach to open system dynamics and review the various notions of quantum non-Markovianity that arise in this paradigm. We then discuss an alternate approach to quantum stochastic processes based on the quantum combs framework, which accounts for multi-time correlations. We discuss the interconnections and differences between these two paradigms, and conclude with a discussion on necessary and sufficient conditions for quantum non-Markovianity.